The Outer Vestibule of the Na(+) Channel–Toxin Receptor and Modulator of Permeation as Well as Gating - Cervenka, René (Molecular Diversity Preservation International, 2010)
The outer vestibule of voltage-gated Na(+) channels is formed by extracellular loops connecting the S5 and S6 segments of all four domains (“P-loops”), which fold back into the membrane. Classically, this structure has been implicated in the control of ion permeation and in toxin blockage. However, conformational changes of the outer vestibule may also result in alterations in gating, as suggested by several P-loop mutations that gave rise to gating changes. Moreover, partial pore block by mutated toxins may reverse gating changes induced by mutations. Therefore, toxins that bind to the outer vestibule can be used to modulate channel gating.